Risk of left atrial appendage thrombus in older patients with atrial fibrillation - Monika Gawałko; Monika Budnik; Beata Uziębło-Życzkowska; Iwona Gorczyca; Paweł Krzesiński; Piotr Scisło; Janusz Kochanowski; Anna Michalska; Olga Jelonek; Katarzyna Starzyk; Agnieszka Jurek; Marek Kiliszek; et al. (Archives of Medical Science, 2021)
Introduction We aimed to compare the prevalence of left atrial appendage (LAA) thrombus and its predictors between old and young patients with atrial fibrillation (AF).